2012
DOI: 10.4056/sigs.2595762
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the rapeseed plant-growth promoting Serratia plymuthica strain AS9

Abstract: Serratia plymuthica are plant-associated, plant beneficial species belonging to the family Enterobacteriaceae. The members of the genus Serratia are ubiquitous in nature and their life style varies from endophytic to free-living. S. plymuthica AS9 is of special interest for its ability to inhibit fungal pathogens of rapeseed and to promote plant growth. The genome of S. plymuthica AS9 comprises a 5,442,880 bp long circular chromosome that consists of 4,952 protein-coding genes, 87 tRNA genes and 7 rRNA operons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The GC-content of the predicted polyketide/nonribosomal peptide operon ranges from 55% to 70% with an average of 61% which is comparable yet slightly higher than in the genus Serratia (52% to 60%) [19]. Blast database searches revealed the presence of an almost identical, unannotated region (99% identities, 99% similarities) in Serratia plymuthica AS12 (GenBank accession number: CP002774 ) [20], Serratia plymuthica AS9 (CP002773) [21] and Serratia sp. AS13 (CP002775).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The GC-content of the predicted polyketide/nonribosomal peptide operon ranges from 55% to 70% with an average of 61% which is comparable yet slightly higher than in the genus Serratia (52% to 60%) [19]. Blast database searches revealed the presence of an almost identical, unannotated region (99% identities, 99% similarities) in Serratia plymuthica AS12 (GenBank accession number: CP002774 ) [20], Serratia plymuthica AS9 (CP002773) [21] and Serratia sp. AS13 (CP002775).…”
Section: Resultsmentioning
confidence: 98%
“…More specifically, they have been shown to inhibit rice seed root and shoot germination [18]. Now, with Serratia plymuthica strain RVH1 and the rapeseed plant-associated Serratia plymuthica AS12 [20], AS13 and AS9 [21], four additional phylogenetically closely related, rhizosphere associated bacterial strains have been identified that harbor the zeamine biosynthesis genes. Therefore, it is plausible that horizontal gene transfer contributed to the spread of the zeamine-producing potential among plant-associated soil bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Signal peptide-containing proteins were identified using the SignalP 4.1 server ( http://www.cbs.dtu.dk/services/SignalP/ , last accessed August 6, 2014) ( Petersen et al 2011 ). For the interspecies comparison, following four genomes were used: S. proteamaculans strain 568 (GenBank accession number CP000826) and S. plymuthica strains AS9 (CP002773) ( Neupane et al 2012 ) and 4Rx13 (CP006250) ( Weise et al 2014 ), which were all isolated from plants, and S. odorifera strain DSM4582 (from human sputum) (ADBY00000000).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several genomes of Serratia spp. with biocontrol ability have been sequenced, and different genetic traits that might be involved in biocontrol mechanisms and their regulation have been reported (Taghavi et al ., ; Neupane et al ., 2012a,b,c; 2013). However, additional functional studies are required to understand regulatory mechanisms involved in biocontrol‐related traits.…”
Section: Introductionmentioning
confidence: 99%